EU enlargement and the race to the bottom of welfare states - Christoph Skupnik (IZA Journal of Migration, 2014)
After the introduction of the freedom of movement for Eastern European workers, EU-15 countries were expected to reduce public benefits in order to avoid becoming "welfare magnets". However, OECD data do not support the prediction of a race to the bottom in benefit levels. Using EU-LFS data, I analyze the determinants of migration flows and do not find evidence that welfare state variables affect migration flows when controlling for temporary political restrictions of the freedom of movement. This explains why the pressure to modify welfare spending is small. Furthermore, evidence is found that the restrictions offset the migration incentive effects of work-related pull factors.
Keywords: F22; J21; J61; 330; Determinants of migration decisions; EU enlargement; "Welfare migration"; Push and pull factors